Implementasi Strategi Manajemen Perubahan - Wahyuni, Sri (Lembaga Yasin AlSys, 2023)
Change management is a systematic process of applying the knowledge, tools and resources needed to effect change in the people who will be affected by the process. In order for change management to run smoothly, it is necessary to have a good strategy, in accordance with the current or future situation and conditions. This writing method was obtained from scientific journals and also trusted books which contain material on the implementation of change management strategies. This research uses the method of literature and analytical studies. The purpose of this journal is to understand more broadly about the implementation of change management strategies. So the conclusion from this discussion is that the implementation of strategic management can make company management more sensitive to external threats (threats from outside). At least strategic management can also prevent various kinds of problems from arising, both from within and from outside the company.